A summary of the second MACR international scientific conference (2nd MSC) - Chua, Eng Wee; Yong, Audrey Chee Hui; Ooi, Der Jiun; Lim, Jonathan Chee Woei; Foo, Jhi Biau; Gopal, Natesan; Lee, Sau Har; Wu, Yuan Seng *; Tan, Shing Cheng; Stanslas, Johnson (Tech Science Press, 2023)
On 7th and 8th December 2022, with easing COVID-related restrictions, the 2nd MACR International Scientific Conference (2nd MSC) took place at the Bandar Saujana Putra Campus of MAHSA University, ensconced in a somewhat secluded part of Greater Kuala Lumpur, away from the downtown hubbub. The meeting is known for its specific focus on cancer-related research. The peace and quiet on campus were perhaps fitting for contemplation of the important question ‘Next-generation cancer therapeutics – Where are we heading?’.